Characterization of the putative wobbly possum disease virus : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Virology at Massey University, Manawatū, New Zealand - Giles, Julia Christine (Massey University, 2017)
The objective of this PhD was to characterise a marsupial arterivirus, termed wobbly possum disease virus (WPDV), and to confirm aetiological involvement of the virus in the development of a neurological disease of the Australian brushtail possum (Trichosurus vulpecula), termed wobbly possum disease (WPD). An in vitro culture system supporting the growth of the virus, comprising primary possum macrophages was developed. Purified virus stock was prepared using iodixanol density gradient ultracentrifugation of infected cell culture lysates and the in vitro growth kinetics of WPDV in primary possum macrophages was investigated using a previously described WPDV-specific RT-qPCR. The steepest increase in the levels of intracellular viral RNA was observed between six and 12 hours post infection, followed by a gradual release of cell-free viral RNA between nine and 24 hours post infection. Maximum levels of intracellular and extracellular viral RNA levels occurred at 24 and 48 hours post infection respectively. Aetiological involvement of the virus in the development of WPD was supported by induction of disease in healthy wild-caught possums following infection with the purified virus. The pathogenesis of viral infection was explored by characterisation of histological lesions and quantification of WPDV RNA in various tissues from experimentally infected possums. Mononuclear inflammatory cell infiltrates of variable size were consistently observed in the liver, kidney, salivary gland and brain. The highest viral RNA levels were found in lymphoid, splenic and liver tissues, suggesting virus tropism for cells of the immune origin, most likely of the monocyte-macrophage system. High levels of viral RNA in tissues and sera from possums euthanased nearly four weeks post-infection indicates that immune response was ineffective in clearing the virus in that time-frame. To investigate the presence of the virus in wild possum populations in New Zealand, an indirect ELISA using Escherichia coli-expressed recombinant viral nucleocapsid (rN) protein as antigen was developed. Pre and post-infection sera from experimentally challenged possums was used for ELISA development. These sera were also characterised using Western-blot against rN antigen. A serological survey of archival possum serum samples that had been collected between the years 2000 and 2016 and from five different regions of New Zealand was also performed using indirect ELISA. Bayesian estimates of parameters for a model of the ELISA data were used to establish ELISA cut-offs for WPDV antibody positive and negative samples. Applying these cut-offs, 50/230 (22%) archival samples were seropositive by indirect ELISA. Altogether, our data suggest that WPDV has been circulating in wild possum populations in New Zealand. Five out of 14 (36%) of pre-infection sera from the challenge study were also seropositive by Western-blot. Development of WPD in these possums following challenge suggests that pre-existing immunity was insufficient for protection against the development of disease. As such, further exploration of virus, host and environmental factors that govern development of disease is required.
Keywords: Nidoviruses; Trichosurus vulpeca; Diseases; New Zealand